INTENSIFICATION IN ENGLISH: FUNCTIONAL, STYLISTIC AND GRAMMATICAL ASPECTS (Web of Teachers: Inderscience Research, 2024)
The article touches upon intensification in English regarding functional, stylistic and grammatical aspects. The study of grammatical and functional-stylistic aspects of intensifiers was carried out using both general scientific methods (description, analysis, synthesis, hypothetical-deductive method) and general linguistic methods (method of analysis of lexicographic sources, passive linguistic observation).